Analisis Yuridis Kekuatan Bukti Elektronik Berdasarkan Hukum Acara Perdata - Gusni Cahaya Putri; Evandito Raihan Prayoga; Abram Sahing; Febri Gumelar (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
The development of information and communication technology has increased the use of electronic documents in legal and business activities, thereby affecting the evidentiary system in Indonesian civil procedural law. This study aims to analyze the legal regulation of electronic evidence and its evidentiary strength in resolving civil cases under Indonesian civil procedural law. The research method used is normative juridical research with statutory and library research approaches. The data were obtained from primary and secondary legal materials and analyzed qualitatively. The results show that electronic evidence has been legally recognized through Law Number 11 of 2008 in conjunction with Law Number 19 of 2016 concerning Electronic Information and Transactions. Its evidentiary strength has the same legal position as other forms of evidence as long as it fulfills the requirements of authenticity, integrity, and validity of electronic data. Therefore, more detailed regulations regarding authentication standards and examination procedures for electronic evidence are still needed to ensure legal certainty in civil court practices.